Future changes in sourcing patterns: 2025 outlook for the Swedish textile industry. Issue 3 (June 2019) - Gadde, Lars-Erik; Jonsson, Patrik
Abstract: This study analyzes ongoing changes in sourcing patterns in offshoring and reshoring, and the reasons thereof. It is based on a survey of expectations regarding changing sourcing patterns from now to 2025 in a sample of 119 Swedish buyers of textiles and apparels. The research approach supplements previous studies primarily focusing on contemporary and historical changes. The most important findings related to the dynamics of sourcing patterns are: (i) increasing sourcing in Europe, and (ii) decreasing sourcing in China, partly substituted by expansion in Bangladesh and other low-cost Asian countries. Increasing sourcing from Europe stems from ambitions to enhance supply chain responsiveness through nearshoring in relation to customers. The changes within Asia represent another pattern: low cost-seeking companies plan to turn to countries with lower costs than China. This pattern illustrates extended offshoring through far-shoring. Consequently, the study shows that both nearshoring and far-shoring represent important sourcing approaches. The resulting patterns show considerable variety owing to diversity in contextual conditions. Social, environmental, and political factors are expected to become increasingly important for future sourcing decisions. Of the firm-internal factors, capabilities related to flexibility and responsiveness are assumed to have the most significant impact. The study shows how these factors in combination with other capabilities, firm size, product assortment, and attitudes to geographical proximity drive various sourcing patterns. Highlights: Description of future expected changes of sourcing patterns for a large group of firms. Explaining the impact of internal and external factors on sourcing decisions. Identification of future sourcing patterns, combining near- and extended far-shoring. Future impact of economic, social, environmental and political factors on sourcing.